Analisis Reformasi Birokrasi untuk Mewujudkan Good Governance pada Pemerintah Kabupaten Pemalang - Mariana Ane Pratiwi; Teguh Yuwono; Retno Sunu Astuti; Teuku Afrizal (PERSPEKTIF, 2022)
The realization of quality services for the welfare of the community is one of the commitments to change through bureaucratic reform, in its implementation conflicts often arise due to inconsistencies. This is what happened in Pemalang Regency, on the one hand the bureaucracy is aggressively carrying out bureaucratic reform as a form of self-improvement, but on the other hand it slows down the progress of the bureaucracy due to the declining culture of service and weak employee integrity. This paper aims to determine the causes of the non-optimal results of the evaluation of bureaucratic reform along with the supporting and inhibiting factors for implementing bureaucratic reform in the Pemalang Regency Government. This paper study uses a qualitative method with case studies. Data was collected through observation, documentation and interviews. The data analysis techniques are: data collection, data reduction, data presentation, data analysis and triangulation and drawing conclusions to test the validity of the data and find objective truth. The results of the study in this paper indicate that the bureaucratic reforms carried out by the Pemalang Regency government have not shown significant signs of increasing towards a more optimal direction in an effort to realize Good Governance, there are still normative problems related to the quality and capacity of the apparatus resources. An increase in commitment and a change in mindset is needed from the leadership to all levels of employees to make fundamental changes and reforms to the government administration system to achieve good governance.